Técnicas computacionais inteligentes para a inferência de estado e a otimização de cultivos de Streptococcus pneumoniae - Horta, Antonio Carlos Luperni (2008)
Streptococcus pneumoniae (pneumococo) is a pathogenic bacterium that causes several infections which are aggravated by the increase of serotypes with antibiotics resistance. The development of an effective vaccine against this pathogen is crucial for the prevention of the neumococcal illnesses. Conjugated vaccines, consisting of the capsular polysaccharide joined to a carrier protein, are more efficient in the stimulation of the immunologic memory. The capsular polysaccharide (PS) is present in the capsule that involves the cell. Thus, the conjugated vaccine elaboration involves bacterial cells cultivation for its production. As the organism is cultivated in the oxygen absence, the lactate production is inevitably high, leading to growth inhibition due to lactate accumulation in the medium. To minimize the inhibitory effects of the lactate accumulation and to increase the PS production it is necessary to monitor the process and adequately control the addition of supplementary medium along with the withdrawal of saturated medium. This kind of operation can be performed by carrying out a fed-bath cultivation in a bioreactor connected to a perfusion system. The success on the monitoring, control and optimization of this bioprocess depends on the efficiency of the modeling and simulation resources employed. This research work considers the uses intelligent computational techniques, specifically the technique of heuristical search called simulated annealing (SA) combined with neural networks for the state inference and the optimization of S. pneumoniae cultivations. The proposal was implemented as a computational system that: a) uses the SA for the identification of the values for a set of parameters associated to unstructured models and; b) uses neural networks (individually and grouped as a committee) for the state inference of a culture. The work presents and discusses the results of the system for data sets experimentally obtained and highlights the importance of the proposal for achieving a higher efficiency in the culture control processes.